2009
DOI: 10.1209/0295-5075/87/47002
|View full text |Cite
|
Sign up to set email alerts
|

Violation of Onsager symmetry for a ballistic channel Coulomb coupled to a quantum ring

Abstract: We investigate a scattering of electron which is injected individually into an empty ballistic channel containing a cavity that is Coulomb coupled to a quantum ring charged with a single-electron. We solve the time-dependent Schrödinger equation for the electron pair with an exact account for the electron-electron correlation. Absorption of energy and angular momentum by the quantum ring is not an even function of the external magnetic field. As a consequence we find that the electron backscattering probabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…An appearance of the magnetic asymmetry of the single electron transfer probability was previously discussed in an bent quantum wire 25 or a cavity 26 asymmetrically connected to terminals. Both papers 25,26 used a time dependent wave-packet approaches and indicated that the asymmetry of the transfer probability arises when the channel electron interacts with the surrounding environment. The present study of the role of the inelastic scattering requires a discussion of the incoming electron of a definite energy rather than the wave packet dynamics.…”
Section: Introductionmentioning
confidence: 83%
“…An appearance of the magnetic asymmetry of the single electron transfer probability was previously discussed in an bent quantum wire 25 or a cavity 26 asymmetrically connected to terminals. Both papers 25,26 used a time dependent wave-packet approaches and indicated that the asymmetry of the transfer probability arises when the channel electron interacts with the surrounding environment. The present study of the role of the inelastic scattering requires a discussion of the incoming electron of a definite energy rather than the wave packet dynamics.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, this magnetoasymmetry effect has been theoretically demonstrated [10][11][12][13][14][15][16][17][18][19][20][21] and experimentally verified. [22][23][24][25][26][27][28][29][30] Magnetoasymmetries arise because the charge response of the system is, generally, not symmetric when the field orientation is inverted.…”
Section: Introductionmentioning
confidence: 84%
“…Away from linear response, the principle of microscopic reversibility is, generally, not satisfied and, as a consequence, the two-terminal current, which consists of lin-ear as well as nonlinear coefficients, is not a symmetric function of B. Recently, this magnetoasymmetry effect has been theoretically demonstrated [10][11][12][13][14][15][16][17][18][19][20][21] and experimentally verified [22][23][24][25][26][27][28][29][30] . Magnetoasymmetries arise because the charge response of the system is, generally, not symmetric when the field orientation is inverted.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the analytic solution of the continuous Schrödinger equation and the Wigner time delay as a quantitative measure of the wave packet dynamics is presented. Closely related subjects are the violation of Onsager's (magnetic field) symmetry in wave packet transport 10,11 and the optical effect called directional birefringence, which features a velocity that depends on the direction of propagation 12 .…”
Section: Non-reciprocity Of the Wigner Time Delaymentioning
confidence: 99%